1996
DOI: 10.2307/3870327
|View full text |Cite
|
Sign up to set email alerts
|

Cold Calcium Signaling in Arabidopsis Involves Two Cellular Pools and a Change in Calcium Signature after Acclimation

Abstract: Cold shock elicits an immediate rise in cytosolic free calcium concentration ([Ca2+]cyt) in both chilling-resistant Arabidopsis and chilling-sensitive tobacco (Nicotiana plumbaginifolia). In Arabidopsis, lanthanum or EGTA caused a partial inhibition of both cold shock [Ca2+]cyt elevation and cold-dependent kin1 gene expression. This suggested that calcium influx plays a major role in the cold shock [Ca2+]cyt response and that an intracellular calcium source also might be involved. To investigate whether the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
580
3
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(616 citation statements)
references
References 0 publications
20
580
3
4
Order By: Relevance
“…Numerous studies have demonstrated that Ca 2+ plays a vital role in the cold‐stress response of plants, for example in Arabidopsis (Knight et al. 1996; Polisensky and Braam 1996; Jakoby et al. 2002), banana (Yang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that Ca 2+ plays a vital role in the cold‐stress response of plants, for example in Arabidopsis (Knight et al. 1996; Polisensky and Braam 1996; Jakoby et al. 2002), banana (Yang et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, a "cold memory" has been described for coldinduced calcium flux in Arabidopsis (Knight et al, 1996). Transfer of Arabidopsis plants to low temperatures results in a rapid, transient increase in free calcium in the cytoplasm, which comes from extracellular and intracellular calcium stores (Knight et al, 1996;Knight and Knight, 2000). Knight et al (1996) have shown that the calcium signature-the peak levels and duration of the calcium influx-is altered upon cold acclimation, becoming diminished in magnitude and prolonged in length.…”
Section: Scripts (mentioning
confidence: 99%
“…Transfer of Arabidopsis plants to low temperatures results in a rapid, transient increase in free calcium in the cytoplasm, which comes from extracellular and intracellular calcium stores (Knight et al, 1996;Knight and Knight, 2000). Knight et al (1996) have shown that the calcium signature-the peak levels and duration of the calcium influx-is altered upon cold acclimation, becoming diminished in magnitude and prolonged in length. The significance here is that the expression of certain cold-regulated genes, including COR and other CBF-targeted genes, appears to involve the action of calcium as second messenger.…”
Section: Scripts (mentioning
confidence: 99%
See 1 more Smart Citation
“…Such measurements have been conducted using Ca 2+ -sensitive fluorescent indicator dyes (e.g. Indo and Fura), the luminescent protein aequorin (Knight et al, 1991(Knight et al, , 1996Legué et al, 1997;Wymer et al, 1997;Cárdenas et al, 2008), and more recently the yellow cameleon (YC) Ca 2+ sensor, a chimeric protein that relies on fluorescence resonance energy transfer (FRET) as an indicator of [Ca 2+ ] cyt changes in the cell (Allen et al, 1999;Miwa et al, 2006;Qi et al, 2006;Tang et al, 2007;Haruta et al, 2008). The YC reporter is composed of cyan fluorescent protein (CFP), the C terminus of calmodulin (CaM), a Gly-Gly linker, the CaM-binding domain of myosin light chain kinase (M13), and a yellow fluorescent protein (YFP; Miyawaki et al, 1997Miyawaki et al, , 1999.…”
mentioning
confidence: 99%